PENGARUH PRODUK DANA TABUNGAN TERHADAP LOYALITAS NASABAH PT. BANK SULUTGO, TBK. CABANG CALACA - SETIAWAN, JESSICA BERNADETTE; SUMAYKU, SONTJE. M. SUMAYKU; Sumampouw, HARRY (Sam Ratulangi University, 2016)
Abstract. the primary variable in this study is a savings product ( X ) and customer loyalty ( Y ) . This study aims to the effect of Product savings fund to customer loyalty of Bank SulutGo Calaca as branch offices. The method used is descriptive quantitative method ,approach using the Spearman rank correlation, to test the significance of the relation between variables and to measure the level of influence that occurs in variable savings products and customer loyalty.Research suggests that the relationship between variable savings product with customer loyalty obtain positive results or categorized as very strong. We hope this research can be used as a reference in subsequent research by developing a variety of other variables related to marketing. Keywords: Savings Product , Customer Loyalty , Customer